Discrimination Identification of Race, Ethnicity and Employment in the Law No. 40 of 2008, Law No. 13 of 2003 in the Civil Code - Hasyim, H.A. Dardiri (Universitas Muhammadiyah Sumatera Barat, 2018)
This study sought to find forms of discrimination in the Law No. 40 of 2008 and Law No. 13 of 2003, and compares them with the Civil Code. This research is using library method. The results show that there are 24 chapters in the Civil Code which are discriminatory. Meanwhile, there are six forms of discrimination in the Law No. 40 of 2008; 17 forms on Law No. 7 of 1984, and 22 form the Law No. 13 of 2003. Discrimination in the Civil Code is contained in 13 forms and 20 articles, in line with 6 forms of international human rights formulations, 22 out of 27 forms of national human rights formulations. The Civil Code in the perspective of human rights can be seen that there are still articles that are discriminatory. This is not in accordance with democracy which contains the principle of non-discrimination.